Новое определение SPARQL — языка запросов Semantic Web - Кургаев, А.Ф. (Доповіді НАН України, 2018)
Дано в метаязыке нормальных форм знаний (НФЗ) текстовое и часть графического описания синтаксиса языка SPARQL структурированных запросов Semantic Web. Наличие таких описаний гарантирует реализуемость языка SPARQL с реализацией интерпретатора метаязыка НФЗ. Показано, что выразительные возможности метаязыка НФЗ для формального описания SPARQL вполне сопоставимы с выразительными возможностями метаязыка Extended Backus-Naur Form. Дано у метамові нормальних форм знань (НФЗ) текстовий і частина графічного опису синтаксису мови SPARQL структурованих запитів Semantic Web. Наявність таких описів гарантує реалізуємість мови SPARQL з реалізацією інтерпретатора метамови НФЗ. Показано, що виразні можливості метамови НФЗ для формального опису SPARQL цілком порівнянні з виразними можливостями метамови Extended Backus-Naur Form. The text and the part of a graphic description of the syntax of the SPARQL structured Query Language for the Semantic Web are described in the metalanguage of normal forms of knowledge. These descriptions guarantee that the SPARQL language can be implemented, when the interpreter of the metalanguage of normal forms of knowledge is implemented. It is demonstrated that the expressive possibilities of the metalanguage of normal forms of knowledge for the formal description of the SPARQL language are quite comparable with those of the Extended Backus-Naur Form Metalanguage.